Capital punishment: a theoretical and cooperative analysis - Ramos, Tainá Corrêa Barbosa (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
Among all the different types of penalties that exist in the various juridical systems around the world, capital punishment, also known as the death penalty, is one of the most controversial ones. The discussion about its legitimacy and legality crosses social, philosophical, cultural, religious and historical fields. The present article aims to first analyze how capital punishment is treated in different parts of the world, whether it is present or not, and to later on focus on the attempts to justify such a harsh punishment, by both the retributive and utilitarian theories of punishment.